2021
DOI: 10.1001/jamaoncol.2021.1144
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Risk of Cardiovascular Disease by Automatic Quantification of Coronary Artery Calcifications on Radiotherapy Planning CT Scans in Patients With Breast Cancer

Abstract: IMPORTANCE Cardiovascular disease (CVD) is common in patients treated for breast cancer, especially in patients treated with systemic treatment and radiotherapy and in those with preexisting CVD risk factors. Coronary artery calcium (CAC), a strong independent CVD risk factor, can be automatically quantified on radiotherapy planning computed tomography (CT) scans and may help identify patients at increased CVD risk.OBJECTIVE To evaluate the association of CAC with CVD and coronary artery disease (CAD) in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 26 publications
3
33
1
Order By: Relevance
“…A multicenter cohort study evaluated the correlation between coronary artery calcium (CAC) and CAD. They found that CAC on breast cancer RT planning CT scan results was associated with CVD, especially CAD, particularly in CAC score > 400 [54]. Treatment of radiation-induced CAD with common revascularization techniques is challenging, as those patients usually have more complex anatomy and disease complexity, scarred and fibrotic grafts and higher rates of postoperative complications, such as poor healing, infections and bleeding, and higher mortality as compared to CAD from other causes [18,19].…”
Section: Coronary Artery Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…A multicenter cohort study evaluated the correlation between coronary artery calcium (CAC) and CAD. They found that CAC on breast cancer RT planning CT scan results was associated with CVD, especially CAD, particularly in CAC score > 400 [54]. Treatment of radiation-induced CAD with common revascularization techniques is challenging, as those patients usually have more complex anatomy and disease complexity, scarred and fibrotic grafts and higher rates of postoperative complications, such as poor healing, infections and bleeding, and higher mortality as compared to CAD from other causes [18,19].…”
Section: Coronary Artery Diseasementioning
confidence: 99%
“…Radiation doses above 30 Gy reportedly increased RIHD by three and a half folds [18,56]. Some of the studies about radiation-related risk factors are summarized in Table 1 [47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64].…”
Section: Radiation-related Risk Factorsmentioning
confidence: 99%
“…Furthermore, emerging data suggest that breast arterial calcification on mammography correlates with CAC, allowing for identification of atherosclerosis and subsequent ASCVD risk ( 34 ). Recently, the BRAGATSTON clinical trial evaluated if automated quantification of CAC on RT planning chest CTs was useful for CVD risk prediction ( 35 , 36 ). The investigators found that automated CAC scoring results might be used as a fast and low-cost tool to identify patients with breast cancer at increased CVD risk ( 36 ).…”
Section: Role Of Cardiac Ct In the Assessment Of Coronary Artery Disease In Cancer Patients And Survivorsmentioning
confidence: 99%
“…Recently, the BRAGATSTON clinical trial evaluated if automated quantification of CAC on RT planning chest CTs was useful for CVD risk prediction ( 35 , 36 ). The investigators found that automated CAC scoring results might be used as a fast and low-cost tool to identify patients with breast cancer at increased CVD risk ( 36 ).…”
Section: Role Of Cardiac Ct In the Assessment Of Coronary Artery Disease In Cancer Patients And Survivorsmentioning
confidence: 99%
“…According to recent findings from Western studies on patients with breast cancer, the CAC score has shown to be predictive in the development of ACE in breast cancer patients [ 15 , 18 ]. However, the value of the CAC score needs to be confirmed and validated in other geographic areas as cardiac diseases have a multifactorial etiology, including race- and patient-specific factors.…”
Section: Introductionmentioning
confidence: 99%